2003
DOI: 10.1016/s0022-5223(03)00698-6
|View full text |Cite
|
Sign up to set email alerts
|

Computational fluid dynamics in the evaluation of hemodynamic performance of cavopulmonary connections after the norwood procedure for hypoplastic left heart syndrome

Abstract: According to these methods, the hemi-Fontan and bidirectional Glenn procedures performed equally well, but important differences in energy losses and flow distribution were found after the completion Fontan procedures. The superior hydraulic performance of the lateral tunnel Fontan operation after the hemi-Fontan procedure relative to any other method may be due to closer to optimal caval offset achieved in the surgical reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
74
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(80 citation statements)
references
References 22 publications
6
74
0
Order By: Relevance
“…This last conclusion was confirmed also in successive studies (Khunatorn et al 2002;Migliavacca et al 1999b;Ryu et al 2001;Bove et al 2003). Most research on the TCPC so far has been done under the hypothesis of steady inlet flows, which is reasonable as they come from systemic venous districts.…”
Section: Modeling Of Vascular Anastomoses In Surgical Procedures For supporting
confidence: 54%
See 1 more Smart Citation
“…This last conclusion was confirmed also in successive studies (Khunatorn et al 2002;Migliavacca et al 1999b;Ryu et al 2001;Bove et al 2003). Most research on the TCPC so far has been done under the hypothesis of steady inlet flows, which is reasonable as they come from systemic venous districts.…”
Section: Modeling Of Vascular Anastomoses In Surgical Procedures For supporting
confidence: 54%
“…Right atrial contraction is usually considered not essential after the TCPC operation, but a certain degree of flow pulsatility may appear as a consequence of: (1) tethering of the intra or extra cardiac conduit due to heart contraction and (2) respiratory effects. As far as we know only few CFD quantitative studies have appeared which include transient flows (Migliavacca et al 1999a;DeGroff and Shandas 2002;Migliavacca et al 2003;Bove et al 2003). The local effects of pulsatile forward flow from the native pulmonary artery on blood flow distribution between the lungs in the BCPA have also been investigated (Migliavacca et al , 1997.…”
Section: Modeling Of Vascular Anastomoses In Surgical Procedures For mentioning
confidence: 99%
“…Numerical techniques allow us to examine the effects of the geometry of the Fontan connection that plays an important role in the overall success of the surgery, and assess blood flow characteristics and energy losses associated with a given surgical design. There are numerous articles on the total cavopulmonary connection simulation (see, e.g., [7,11,22,25,26]) that do a very careful CFD analysis on complex patient-specific configurations in an attempt to answer some of these questions. Some of the earlier work in computational fluid dynamics applied to congenital heart disease compared energy loss in the standard "t" junction Fontan with the proposed "offset" model, and led to the adoption of the offset model as the currently preferred method [9,10,28,29].…”
mentioning
confidence: 99%
“…CFD has also been employed to compare hydraulic performance between the hemi-Fontan and bidirectional Glenn procedures, as well as the various types of completion Fontan operations. 29) Based on 3D anatomical mesh models derived from image data of various sources, it was shown that the hemi-Fontan and bidirectional Glenn procedures performed almost identically, in spite of the fact that important differences in energy losses and flow distribution were found after the completion of Fontan procedure. Moreover, the lateral tunnel FO showed superior hydraulic performance after the hemi-Fontan, possibly due to closer to optimal caval offset achieved in the surgical reconstruction.…”
Section: Computational Fluid Dynamics Studiesmentioning
confidence: 99%